Bowenoid Papulosis of the Genitalia in an Older Individual: A Case Report - Reza Kazemi; Faezeh Jandaghi; Maryam Derakhshan; Moein Bighamian; Farzaneh Montazeri (Advanced Biomedical Research)
Bowenoid papulosis (BP) is an uncommon condition caused by human papillomavirus, presenting as an asymptomatic lesion on the anogenital region. We report a case of BP in a 63-year-old male, an unusual demographic for this condition. Clinically, BP lesions resemble viral warts. Although BP has a low risk of progression to invasive squamous cell carcinoma (SCC), prompt diagnosis and management are crucial to prevent malignant transformation. Treatment options include topical therapies, laser therapy, and surgical excision. This case highlights the importance of recognizing BP and implementing appropriate management strategies, especially in atypical age groups and individuals with predisposing factors.